HIPODONCIA: REPORTE DE UN CASO FAMILIAR (2018)
Hypodontia is defined as the ausence of one to six teeth, without considering third molares; it is an event that happens, in the permanent teething, between the 1.6% to 9.6% as much in men as in women. A case of family hypodontia is reported with a pattern of inheritance autosomal recessive, with absence of lateral incisive 22, and second premolar in the four quadrants besides the third molars and microdontia of lateral incisive 12.